Of tourists and vagabonds in the Global South : marginality and tourism in Buenos Aires City - Korstanje, Maximiliano E. (Emerald Publishing Limited, 2024)
Zygmunt Bauman has historically debated the inconsistencies of global capitalism in his different texts and offered a diagnosis of global capitalism based on two main figures: tourists who are privileged agents legally encouraged to move and visit the world and vagabonds who are closely scrutinized and subject to a climate of oppression and immobility. With a focus on Buenos Aires city, Maximiliano E. Korstanje critically explores the position of marginality and homeless people and how they are located alongside urban tourist resorts or luxury hotels. Offering a lucid diagnosis of the conflictive encounter between people experiencing homelessness and foreign tourists in Buenos Aires City, the chapters examine divergent topics such as poverty tourism, safety-security in tourism, tourism consumption, heritage tourism, and anthropology of tourism. The Tourism Security-Safety and Post Conflict Destinations series provides an insightful guide for policy makers, specialists and social scientists interested in the future of tourism in a society where uncertainness, anxiety and fear prevail.
Keywords: Urban tourism -- Argentina -- Buenos Aires.; Tourism -- Argentina -- Buenos Aires.; Homelessness -- Argentina -- Buenos Aires.; Tourism -- Economic aspects.; Rogues and vagabonds -- Argentina -- Buenos Aires.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Hospitality, sports, leisure and tourism industries.; elektronické knihy; electronic books